Polymer Science and Engineering Using Deep Eutectic Solvents - Roda, Ana (Polymers (Basel), 2019)
The green and versatile character of deep eutectic solvents (DES) has turned them into significant tools in the development of green and sustainable technologies. For this purpose, their use in polymeric applications has been growing and expanding to new areas of development. The present review aims to summarize the progress in the field of DES applied to polymer science and engineering. It comprises fundamentals studies involving DES and polymers, recent applications of DES in polymer synthesis, extraction and modification, and the early developments on the formulation of DES–polymer products. The combination of DES and polymers is highly promising in the development of new and ‘greener’ materials. Still, there is plenty of room for future research in this field.